Local Wisdom of Batak Culture in Supporting the Tolerance Character of the Tapanuli Society - Aini, Saripah; Akmal, Akmal (MUHARRIK: Jurnal Dakwah dan Sosial, 2022)
This article discusses how the local cultural wisdom of the Batak ethnic group in Lumut District, Central Tapanuli Regency, such as in weddings, deaths, and other holidays contains a very high value of tolerance. This strength is inseparable from the Batak ethnic kinship value system, known as Dalihan na tolu. The kinship system outlines and establishes very detailed rules for social relations for the Batak ethnic. This article uses a qualitative research method using an ethnographic approach. This approach as described by Malinowski seeks to describe and build the socio-cultural structure of a society and compare social systems to obtain general rules about a society. This study has a purpose: (1) revealing the values ​​of local wisdom of the Batak ethnic in Lumut District, Central Tapanuli Regency in supporting tolerance, (2) identifying what factors support the character of tolerance in the life of the Batak ethnicity in Lumut District. , Central Tapanuli Regency, (3) describes the social life of the Batak ethnic in Lumut District, Central Tapanuli Regency. Based on the research results in this article, the authors get the results that the social relations possessed by the Batak ethnic in Lumut District have succeeded in bringing a high tolerance attitude. So that it forms community behavior that respects each other and can live side by side regardless of ethnic or religious background.